2002
DOI: 10.2151/jmsj.80.733
|View full text |Cite
|
Sign up to set email alerts
|

The Bimodality of the 100 hPa South Asia High and its Relationship to the Climate Anomaly over East Asia in Summer.

Abstract: The NCEP/NCAR pentad mean reanalysis data from 1980 to 1994 are employed to examine the activities of the 100 hPa South Asia High (SAH) during the boreal summer. The results show that there exists bimodality in the longitude location of the SAH. According to the two preferred regions for the SAH, the SAH is classified into the Tibetan Mode (TM) and the Iranian Mode (IM), respectively. The studies on the maintenance mechanism, both from circulation structure and thermal structure, manifest that the SAH has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
161
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 5 publications
9
161
1
Order By: Relevance
“…[34] The bimodality in the location of the anticyclone found in earlier studies [Zhang et al, 2002] in 100 hPa geopotential height is not reflected in the 360 K (i.e., about 150 hPa) low PV area investigated here (see Figure 6, top panel). At 380 K, which is closer to 100 hPa as used in Zhang et al [2002], the probability distribution of low PV air shows two maxima, one at around 50 ı E and one around 105 ı E (see Figure 15).…”
Section: Summary and Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…[34] The bimodality in the location of the anticyclone found in earlier studies [Zhang et al, 2002] in 100 hPa geopotential height is not reflected in the 360 K (i.e., about 150 hPa) low PV area investigated here (see Figure 6, top panel). At 380 K, which is closer to 100 hPa as used in Zhang et al [2002], the probability distribution of low PV air shows two maxima, one at around 50 ı E and one around 105 ı E (see Figure 15).…”
Section: Summary and Discussionmentioning
confidence: 50%
“…At 380 K, which is closer to 100 hPa as used in Zhang et al [2002], the probability distribution of low PV air shows two maxima, one at around 50 ı E and one around 105 ı E (see Figure 15). However, low PV area at 380 K as diagnostic for the anticyclone strength suffers from the following deficit: Over the summer season, mean PV in the monsoon region increases.…”
Section: Summary and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The same bimodal high pressure anomalies can also be seen at 200 hPa in the upper troposphere (not shown). In contrast, Zhang et al (2002) showed the existence of bimodality in the longitude of the South Asia High in northern summer. Statistical inspection of the South Asian High by Zhang et al (2002) reveals the Tibetan mode (near 90 E) and Iranian mode (near 60 E).…”
Section: Climatological Fieldsmentioning
confidence: 80%
“…In contrast, Zhang et al (2002) showed the existence of bimodality in the longitude of the South Asia High in northern summer. Statistical inspection of the South Asian High by Zhang et al (2002) reveals the Tibetan mode (near 90 E) and Iranian mode (near 60 E). The results by Zhang et al (2002) for the climatological field and our findings for anomaly fields (Fig.…”
Section: Climatological Fieldsmentioning
confidence: 80%